2021
DOI: 10.5771/0943-7444-7-8-535
|View full text |Cite
|
Sign up to set email alerts
|

Science Mapping and Science Maps

Abstract: Science maps are visual representations of the structure and dynamics of scholarly knowl­edge. They aim to show how fields, disciplines, journals, scientists, publications, and scientific terms relate to each other. Science mapping is the body of methods and techniques that have been developed for generating science maps. This entry is an introduction to science maps and science mapping. It focuses on the conceptual, theoretical, and methodological issues of science mapping, rather than on the mathematical for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 1 publication
0
7
0
2
Order By: Relevance
“…The final step was the interpretation of the science maps, which required close collaboration among experts in the mapped area, with the goal of not only quantitatively counterpart the qualitative knowledge of domain experts but also providing new insights and useful knowledge for research and science policy purposes, as suggested by [82,83]. The workflow of the science mapping methodology applied in this study is shown in Figure 5.…”
Section: Methodsmentioning
confidence: 99%
“…The final step was the interpretation of the science maps, which required close collaboration among experts in the mapped area, with the goal of not only quantitatively counterpart the qualitative knowledge of domain experts but also providing new insights and useful knowledge for research and science policy purposes, as suggested by [82,83]. The workflow of the science mapping methodology applied in this study is shown in Figure 5.…”
Section: Methodsmentioning
confidence: 99%
“…A collaboration analysis helps to understand the social ties within a field. Co‐authorship networks are the most common indicators of social structure (Peters & Van Raan, 1991) and help to investigate scientific collaborations within a field (Petrovich, 2020). RQ3 was addressed by determining THCCR's intellectual structure that identifies the ‘most influential works in the field and traces the intellectual evolution of the field by tracking changes in citation patterns over time’ (Ramos‐Rodríguez & Ruíz‐Navarro, 2004).…”
Section: Methodsmentioning
confidence: 99%
“…To carry out the present analysis we have used a specific methodological framework for science mapping, based on the approach of Petrovich (2021), who recovers from Börner, Chen, and Boyack (2005) a logical sequence appropriate for our study (data collection, pre-processing, normalization, visualization, enrichment, interpretation, and reuse).…”
Section: Digital Humanities In the Global Landscapementioning
confidence: 99%